Efficacy and Safety of Erythromycin in the Treatment of Mycoplasma Pneumonia in Children: A Systematic Review and Meta-Analysis - Mingxiu Sun
The effectiveness and safety of erythromycin for treating mycoplasma pneumonia in pediatric patients is a subject of significant interest. This study aims to conduct a systematic review and meta-analysis to assess the efficacy and safety of erythromycin in the treatment of mycoplasma pneumonia in children, with the goal of providing evidence-based recommendations for pediatric care.